Antimicrobial resistance pattern in aerobic bacteria isolated from endotracheal aspirate in ventilator-associated pneumonia: Ten years observation from a tertiary care hospital - Surlu Vidya Rao; Karadka Ramdas Thilakchand; Rekha Boloor; Sucharitha Suresh; Thomas George; Michael LJ. Pais; Ramakrishna Pai Jakribettu; Manjeshwar Shrinath Baliga (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Ventilator-associated pneumonia (VAP) is a nosocomial infection associated with high morbidity and mortality. This study was undertaken to monitor the trend of the demographical details, comorbid conditions, bacterial etiological agents, and their antibiogram causing VAP in adults in the year 2008, 2013 and 2018. Material and Methods: A retrospective study conducted at the Department of Microbiology, Hospital Infection control and Quality Control at a tertiary care teaching hospital. All the adult patients with more than 48 h of the mechanical ventilator with endotracheal intubation with Clinical Pulmonary infection Score >6 with suspicion of VAP were included in the study at a difference of 5 years, i.e., 2008, 2013, and 2018. Results: A total of 338 patients were included in the study, of which males accounted for more than two-third of the patients studied. Nearly 45% of the patients belonged to geriatric (>60 years) age group. The most common comorbid conditions were chronic obstructive pulmonary disease, hypertension and diabetes mellitus. Among the gram-negative isolates, Klebsiella pneumoniae, Acinetobacter species, and Pseudomonas aeruginosa were the most common. There is an emergence of resistance to most commonly administered antimicrobial agents like aminoglycosides, levofloxacin, piperacillin/tazobactum, and carbapenems during the study period. Conclusion: This is a ten-year study on the antibiotic resistance pattern of organisms causing VAP. As far as the authors are aware, this is the first study addressing the pattern of change in drug resistance in the organisms causing VAP over a decade. The emergence of multi-drug resistant (MDR) MDR pathogens, especially in intensive care unit (ICU), is a great concern for the intensivist and infection control physicians. Preventive measures need to be undertaken to control the spread of these pathogens to the patients in the ICU.